A Comparison of Soft Tissue Face Analysis Measurements with Face Analysis Measurements in 3-D Modelling - İsmet Emrah Emre; Kerem Sami Kaya; Mehmet Veli Karaaltın (The Turkish Journal of Ear Nose and Throat)
Objective: The face is the most important factor determining the physical appearance of individuals. Measurements of facial beauty have continuously been made and evaluated on two-dimensional, photographs. As an alternative method, the evaluation of facial morphology could be better determined using 3D technology. The aim of this study was to assist in facial analysis by measuring the soft tissue facial ratios in our society in order to compare these values with the proportions and measurements of the 3D facial model of the patient. Materials and Methods: A total of 24 (10 male, 14 female) subjects’ faces and their 3D masks were measured to compare the results of each measurement. Results: There was a significant difference between the soft tissue measurements and 3D measurements of only the dorsal width measurements of male patients (p=0.019) and columellar length and upper lip width measurements of women (p=0.021, p=0.035), while other facial analysis measurements showed no significant differences. Additionally, no significant difference other than the upper width, nasolabial angle, and lateral intercantal distance measurements were noted in the 3D mask (p=0.026, p=0.022, p=0.042). Conclusion: This study examined the compatibility of the 3D-printed models and soft tissue measurements. We found no significant difference except for the dorsal width measurements of male patients and the columellar length and upper lip width measurements of female patients. These results suggest that modelling with 3D printing is technologically safe and advantageous and has great potential in facial aesthetics and surgical interventions.